Strategi Islamic Human Capital Management Dalam Peningkatan Kinerja Pegawai Bank Syariah Indonesia - Ade Yuliar (Bertuah: Journal of Sharia and Islamic Economics, 2021)
The rapid development of Islamic banking with the emergence of Indonesian Sharia Banks must be supported by qualified human capital. However, in reality, there is still a lack of qualified Islamic bank human resources who have a comprehensive understanding of Islamic principles. This study aims to explore Islamic human capital management and try to propose possible solutions to overcome problems related to improving the performance of Islamic bank human resources using a qualitative approach. This study concludes that Islamic human resource management must be implemented properly in Islamic banks. Islamic banks must have a fair recruitment and selection system, instill Islamic values in the corporate culture, increase employee commitment and loyalty through a benefit compensation system, establish KPIs and optimize training and development.